Characterization of the clinical and immunologic phenotype and management of 157 individuals with 56 distinct heterozygous NFKB1 mutations - BARIŞ, SAFA (MOSBY-ELSEVIER, 2020)
Background: An increasing number of NFKB1 variants are being identified in patients with heterogeneous immunologic phenotypes. Objective: To characterize the clinical and cellular phenotype as well as the management of patients with heterozygous NFKB1 mutations. Methods: In a worldwide collaborative effort, we evaluated 231 individuals harboring 105 distinct heterozygous NFKB1 variants. To provide evidence for pathogenicity, each variant was assessed in silico; in addition, 32 variants were assessed by functional in vitro testing of nuclear factor of kappa light polypeptide gene enhancer in B cells (NF-kappa B) signaling. Results: We classified 56 of the 105 distinct NFKB1 variants in 157 individuals from 68 unrelated families as pathogenic. Incomplete clinical penetrance (70%) and age-dependent severity of NFKB1-related phenotypes were observed. The phenotype included hypogammaglobulinemia (88.9%), reduced switched memory B cells (60.3%), and respiratory (83%) and gastrointestinal (28.6%) infections, thus characterizing the disorder as primary immunodeficiency. However, the high frequency of autoimmunity (57.4%), lymphoproliferation (52.4%), noninfectious enteropathy (23.1%), opportunistic infections (15.7%), autoinflammation (29.6%), and malignancy (16.8%) identified NF-kappa B1-related disease as an inborn error of immunity with immune dysregulation, rather than a mere primary immunodeficiency. Current treatment includes immunoglobulin replacement and immunosuppressive agents. Conclusions: We present a comprehensive clinical overview of the NF-kappa B1-related phenotype, which includes immunodeficiency, autoimmunity, autoinflammation, and cancer. Because of its multisystem involvement, clinicians from each and every medical discipline need to be made aware of this autosomal-dominant disease. Hematopoietic stem cell transplantation and NF-kappa B1 pathway-targeted therapeutic strategies should be considered in the future.
Keywords: NFKB1 variant; NFKB1 mutation; common variable immunodeficiency; reduced penetrance; NF-kappa B1-related phenotype; autosomal dominant; NF-KAPPA-B; NUCLEAR-FACTOR; NF-KAPPA-B1; HAPLOINSUFFICIENCY; IMMUNODEFICIENCY; CELLS